Identifikasi Bidang Gelincir di Dusun Dukuh, Desa Koripan, Kecamatan Matesih, Kabupaten Karanganyar, Menggunakan Metode Geolistrik Resistivitas Konfigurasi Wenner Alfa - Irwan Romadon; Darsono D; Sorja Koesuma (Department of Physics, Sebelas Maret University, 2017)
Slip surface identification in Dukuh, Koripan Village, Matesih Sub-district, Karanganyar District has been conducted with geoelectrical resistivity method with Wenner Alfa configuration. Data acquisitions was done on 5 sample lines. The length of each line is 75 meter. The smallest electrode spacing’s 3 meter, with multiplier (n) between 1 to 5. Two dimensional results show that slip surface in every sample lines formed by watertight wet clays material, with resistivity 8,99 Ωm until 13,4 Ωm. The depth of the slip surface in each line is varies. Slip surface of the line 1 was found at a depth of 1 meter to 3,7 meter, the line 2 was found at 2 meter to 4 meter, the line 3 was found at 0,75 meter to 3,78 meter, the line 4 was found at 1,5 meter to 3,5 meter, and the slip surface of line 5 was found at 0,75 meter to 3 meter. Three dimenisonal result show that the area with high land movement was covered by sandy-clay materials.